Manifestations of Cultural Imperialism in Selected Short Stories by Ngugi Wa Thiong'o - الحربي، عائشة عبيد مطلق (جامعة الملك عبدالعزيز, 2023)
الهدف من هذه الدراسة هو تسليط الضوء على الاستعمار الثقافي الأجنبي وتأثيره المدمر على الثقافة الأفريقية المحلية. وسيتم تحقيق ذلك من خلال تحليل وتفسير مختلف مظاهر الإمبريالية الثقافية التي تنعكس في قصص نغوغي وا ثيونغو القصيرة في كتابه "حياة سرية" (1975). ومن الأمور الأساسية في معالجة هذا الموضوع هو دراسة دور الكاتب الأفريقي في حماية الثقافة المحلية من الانتهاك السافر للقيم الغربية. وتتفاقم حدة هذه المظاهر المختلفة للإمبريالية الثقافية بسبب تغلغل القيم الأجنبية في الثقافة المحلية، وإدخال نظام اجتماعي واقتصادي أجنبي على أفريقيا، وكذلك ظهور طبقة النخبة الأفريقية التي تحل محل المستعمر الأجنبي المغادر. وتناقش الدراسة موقف نغوغي الذي لا هوادة فيه تجاه الإمبريالية الثقافية والذي كان مدفوعا بإحساسه بالالتزام الأخلاقي لرفع وعي الناس بأهمية حماية ثقافتهم من التأثير المدمر للقوى الأجنبية وذلك من أجل خلق الأمل بمستقبل أفضل. The aim of the present study is to explore cultural imperialism and its ruinous impact on native African culture. This is achieved through the analysis and interpretation of various manifestations of cultural imperialism reflected in Ngugi wa Thiong'o short stories in Secret lives (1975). Central to the treatment of this topic is an examination of the African writer's role in protecting native culture from the evil infringement of Western values. The various modes of cultural imperialism are exacerbated by the penetration of foreign values into native culture, the introduction of a socio-economic system which is alien to Africa, and the rise of an African elite-class who replace the departing foreign exploiters. The paper argues that Ngugi's relentless attitude towards cultural imperialism is motivated by his sense of moral commitment to raise people's awareness about the importance of protecting their culture from the disrupting influence of foreign power so as to create hope for a better future.
Keywords: الإمبريالية الثقافية -- القصص القصيرة -- الثقافة المحلية -- أفريقيا